Principles of Human Rights (HAM) in Indonesian Sustainable Palm Oil (ISPO) - Ratu bilqis Naily Hidayah; Waro Satul Auliyak (Indonesian Journal of Law and Islamic Law (IJLIL), 2023)
Palm oil is Indonesia's leading commodity that is able to compete in the international market. However, there are often accusations that Indonesian palm oil is unsustainable due to problems of deforestation, corruption and human rights violations against land grabbing of indigenous and local communities. So that they lose their homes and find it difficult to meet their needs because they depend on the forest. In response to this, the government has updated the ISPO regulations through Presidential Regulation Number 44 of 2020 concerning the Indonesian Sustainable Palm Oil plantation certification system. The formulation of the problem from this research is whether ISPO is in accordance with human rights principles and what is the future conception so that ISPO is more in line with human rights principles. This research is included in normative legal research using a legal and conceptual approach. Based on the research results, it is known that ISPO has complied with several human rights principles, such as universal principles and non-discrimination. ISPO principles and criteria should be adjusted to the capacity of independent smallholders, so that there is equality in efforts to increase oil palm production.